Analisis Potensi Kewirausahaan Mahasiswa Universitas Batanghari - Devita, Reni; Emil, Muhammad; Azima, Khuluqon; Rasdi, Rasdi (Universitas Batanghari Jambi, 2024)
By employing descriptive analysis and questionnaires distributed to all Batanghari University students, this study seeks to ascertain the entrepreneurial potential analysis of the student body. As part of the entrepreneurship education plan in higher education, the Entrepreneurial Student Program (PMW) was created to promote an entrepreneurial spirit and encourage entrepreneurial activity so that college graduates become more job creators. On the other hand, it is uncommon to discover a graduate who wishes to launch his business as soon as he graduates from college. The failure of this endeavor is said to have resulted from a lack of seriousness in attempting and appreciating pupils' potential. Six criteria can be used to evaluate a student's entrepreneurial potential: personality, self-control, creativity, drive or desire, risk-taking daring, and self-assurance. Recognizing a student's potential might, in some ways, give insight into how much they believe they still need to study in order to become even better. Gaining awareness of your entire being, including your advantages and shortcomings, is what it means to know oneself. These insights might prove invaluable in your entrepreneurial endeavors.